System dynamics modelling and its implications for childhood obesity prevention: evidence from improving the consumption of portion size and meal frequency - Zainal Abidin, Norhaslinda; Mamat, Mustafa; Tengku Izham, Tengku Hizam; Dangerfield, Brian; Baten, Md Azizul (Hikari Ltd, 2014)
The childhood obesity has rapidly increased,though little is known about the impact of frequency of meals and portion size on weight and obesity.The objective of this study is to compare and to determine the effective strategy for obesity prevention by improving the consumption of portion size and meal frequency.This study utilised the secondary data obtained from the Health Survey for England for the child population aged between 2 to 15 years in United Kingdom This study combines the different strands of knowledge from nutrition, physical activity and body metabolism and synthesizing this knowledge into a system dynamics model which the model offers unique insights into the cause-and-effect relationships among the influencing factors. Findings from the simulation analysis demonstrated that reducing meal frequency is the most effective controlling strategy for obesity prevention. This is asserted by the fact that the highest reduction in average weight (3.14%-4.5%) and average body mass index (3.14%-4.5%) between 2020 and 2030 was observed by improving meal frequency.This paper concludes that system dynamics utilised in this study will be advantageous to guide the food stakeholder to gain insight into the complex of eating behavior and to experiment with various intervention strategies for obesity prevention.